PENGARUH KEPEMIMPINAN, MOTIVASI, KEPUASAN KERJA DAN KONFLIK PEKERJAAN-KELUARGA TERHADAP KINERJA KARYAWAN (Studi pada PT. Bank Pembangunan Daerah Jawa Tengah Cabang Utama Semarang) - Okky Tri Cahyo Utomo, 10.05.51.0096 (Students Journal of Economic and Management, 2015)
This study analyzed the effects of work leadership, motivation, job satisfaction, work-family conflict on employee performance. The research object in this paper is PT.Bank Pembangunan Daerah Jawa Tengah Cabang Utama Semarang. Sampling technique was used in this study or the overall employee population data totaling 100 respondents to the method of data collection using a questionnaire (questionnaire) by spreading the list of statements to the respondents in order to obtain information. The research objective was formulated to seek answers to the flow that affect employee performance. The data were analyzed using factor analysis to test the validity of the question items with loading factor > 0,4, Cronbach alpha formula to test the reliability of the instrument with reliability coeficients > 0,7 , regression analysis, to examine the influence of each partial independent variables were tested by regression analysis. The results of the research are: (1) Leadership has a positive and significant impact on employee performance. (2) Motivation has an influence on employee performance. (3) Job Satisfaction has a positive and significant impact on employee performance. (4) Work-Family Conflict has a positive and significant impact on employee performance. Keywords: work leadership, motivation, job satisfaction, work-family conflict andÂ employee performance.